A Pengaruh Kepuasan Kerja terhadap Kinerja Karyawan Dimediasi oleh Disiplin Kerja - Triastutik, Julaika; Sarwoko, Endi; Sedyastuti, Kristina (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2024)
One of the challenges for companies is creating human resources with optimal performance supported by a high level of job satisfaction. Job satisfaction plays a crucial role in enhancing employee discipline, as employees who feel satisfied and happy with their work tend to demonstrate better performance. This study aims to analyze the effect of job satisfaction on employee performance, with work discipline as a mediating variable, at the Land Office of Malang Regency. The study employs a quantitative approach, with data collected through questionnaire distribution. The sampling technique used is total sampling, involving all civil servant employees at the Land Office of Malang Regency, totalling 37 respondents. The results of the analysis reveal that job satisfaction has a positive and significant effect on employee performance, as well as on work discipline. Additionally, work discipline positively and significantly affects employee performance while mediating the relationship between job satisfaction and employee performance. The implications of this study suggest that companies should focus on improving job satisfaction through development programs, recognition, and incentives, as this can indirectly enhance employee performance by increasing work discipline.